2012
DOI: 10.1095/biolreprod.111.095877
|View full text |Cite
|
Sign up to set email alerts
|

Function of the Acrosomal Matrix: Zona Pellucida 3 Receptor (ZP3R/sp56) Is Not Essential for Mouse Fertilization1

Abstract: In mammalian fertilization, sperm-zona pellucida binding is considered to be a critical aspect of gamete interaction. In this study, we examine the mouse sperm acrosomal matrix protein zona pellucida 3 receptor (ZP3R; formerly called sp56) because of our interest in defining the function of the acrosomal matrix, the particulate compartment within the sperm secretory acrosome. Using targeted deletion of the Zp3r gene by homologous recombination, we examined the fertility of nullizygous animals. Our experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 30 publications
3
38
0
Order By: Relevance
“…Moreover, glycosylation was not observed on these residues on native ZP proteins (Boja et al, 2003). Furthermore, disruption of the ZP3-binding protein SP56 (ZP3R -Mouse Genome Informatics) on spermatozoa (Bookbinder et al, 1995) resulted in almost no phenotype in fertilization (Muro et al, 2012). Finally, enzymes that make core glycans have also been disrupted, and eggs lacking complex and hybrid N-glycans as well as core-1-derived O-glycans were fertilized normally (Shi et al, 2004;Williams et al, 2007).…”
Section: The Zona-binding Ability Of Spermatozoamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, glycosylation was not observed on these residues on native ZP proteins (Boja et al, 2003). Furthermore, disruption of the ZP3-binding protein SP56 (ZP3R -Mouse Genome Informatics) on spermatozoa (Bookbinder et al, 1995) resulted in almost no phenotype in fertilization (Muro et al, 2012). Finally, enzymes that make core glycans have also been disrupted, and eggs lacking complex and hybrid N-glycans as well as core-1-derived O-glycans were fertilized normally (Shi et al, 2004;Williams et al, 2007).…”
Section: The Zona-binding Ability Of Spermatozoamentioning
confidence: 99%
“…However, the gene disruption of these factors resulted in no significant phenotype in fertilization [e.g. GalTase (Lu and Shur, 1997), Sp56 (Muro et al, 2012), zonadhesin (Tardif et al, 2010), Crisp1 (Da Ros et al, 2008, acrosin (Baba et al, 1994)]. Thus, although these factors may play a role in inducing the acrosome reaction, the importance of these factors, and a zona-induced acrosome reaction, during fertilization is unclear.…”
Section: Regulation and Importance Of The Zona-induced Acrosome Reactionmentioning
confidence: 99%
“…Disruption of these proteins like zonadhesin (Zan) [11], 毬 1,4-galactosyltransferase-I [16], and ZP3R [17] do not make the null individual sterile. However, Zannull mice sperm exhibit a loss of species-specific properties; thus, these sperm can bind to the egg cells of other species.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the knockout mice of PH-20 (Baba et al 2002) and clusterin (Bailey et al 2002) discussed in the previous paragraphs showed normal fertility. Moreover, unexpectedly, gene-targeting of the C4BP-related protein, ZP3R/sp56, had no effect on mouse fertilization, and it has been suggested that the sperm-zona pellucida binding system might be functionally redundant (Muro et al 2012). The sperm maturation system is likely to involve multiple redundant proteins, and C4BP might be one of them.…”
Section: Discussionmentioning
confidence: 99%